Hubungan Riwayat Keluarga dengan Kejadian Vitiligo di Rumah Sakit Mayapada Tangerang Tahun 2019 - 2024 - Sirait, Nathasya; Tan, Sukmawati Tansil (Jurnal MedScientiae, 2025)
Vitiligo is an autoimmune disorder characterized by the loss of melanocytes, leading to the appearance of white patches on the skin. This study aimed to investigate the relationship between family history and parental consanguinity with the clinical manifestations of vitiligo. A cross-sectional descriptive-analytic design was used, involving 197 vitiligo patients at Mayapada Hospital Tangerang from 2019 to 2024. Data were collected through medical records and structured questionnaires, then analyzed using the Chi-Square test and Odds Ratio calculations. The most common clinical types were vulgaris (33.0%) and universalis (32.0%). A total of 46.7% of respondents had a family history of vitiligo, and 21.8% had parents with a consanguineous relationship. A statistically significant association was found between family history and clinical type (p = 0.042), and a highly significant association between parental consanguinity and family history of vitiligo (p < 0.001). The Odds Ratio of 7.241 indicated that parental consanguinity considerably increases the risk of vitiligo occurring within families. These findings suggest that genetic factors play a substantial role in the clinical expression of vitiligo.